An EAV-HP insertion in the promoter region of SLCO1B3 has pleiotropic effects on chicken liver metabolism based on the transcriptome and proteome analysis - Jianfei Chen (Nature Portfolio, 2021)
Abstract Solute carrier organic anion transporter 1B3 (SLCO1B3) is an important liver primarily highly expressed gene, its encoded protein (OATP1B3) involved in the transport of multi-specific endogenous and exogenous substances. We previously reported that an EAV-HP inserted mutation (IM+) in the 5ʹ flanking region of SLCO1B3 was the causative mutation of chicken blue eggs, and a further research showed that IM+ significantly reduced the expression of SLCO1B3 in liver. Herein, we confirmed a cholate response element (IR-1) played an important role in activating SLCO1B3 and in vitro experiments showed that the activation of IR-1 can be significantly reduced by the EAV-HP IM+ . We performed transcriptome and proteomic analysis using the same set of IM+ and IM− liver tissues from Yimeng hens (a Chinese indigenous breed) to study the effect of SLCO1B3 and OATP1B3 expression reduction on chicken liver function. The results showed that common differential expression pathways were screened out from both transcriptome and proteome, in which fatty acid metabolism and drug metabolism—cytochrome P450 were significantly enriched in the KEGG analysis. The lipid-related metabolism was weakened in IM+ group, which was validated by serum biochemical assay. We unexpectedly found that EAV-HP fragment was highly expressed in the liver of the IM+ chickens. We cloned the EAV-HP full-length transcript and obtained the complete open reading frame. It is worth noting that there was some immune related differential expressed genes, such as NFKBIZ, NFKBIA, and IL1RL1, which were higher expressed in the IM+ group, which may due to the high expression of EAV-HP. Our study showed that EAV-HP IM+ reduced the expression of SLCO1B3 in liver, resulting in the decrease of fatty metabolism and exogenous substance transport capacity. The mutation itself also expressed in the liver and may be involved in the immune process. The mechanism needs further study.